2018
DOI: 10.1021/acsami.8b06598
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanomedicine with “Lego” Surface Allowing Modular Functionalization and Drug Encapsulation

Abstract: Surface functionalization of nanoparticles (NPs) is of pivotal importance in nanomedicine. However, current strategies often require covalent conjugation that involves laborious design and synthesis. Herein, cucurbit[7]uril (CB[7])-decorated poly(lactic acid) (PLA)/poly(lactic-co-glycolic acid) (PLGA) NPs are developed and exploited for the first time as a novel, biocompatible, and versatile drug delivery platform with a noncovalently tailorable surface. CB[7] on the surface of NPs, acting as a "Lego" base blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 54 publications
(75 reference statements)
0
44
0
Order By: Relevance
“…al. reported a coassemble of an CB[7]‐decorated poly(lactic acid) CB3 and poly(lactic‐co‐glycolic acid) (PLGA) based NPs as a novel drug delivery platform . A hydrophobic anticancer drug PTX was loaded into the NPs.…”
Section: Amphiphilic Cbs For Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…al. reported a coassemble of an CB[7]‐decorated poly(lactic acid) CB3 and poly(lactic‐co‐glycolic acid) (PLGA) based NPs as a novel drug delivery platform . A hydrophobic anticancer drug PTX was loaded into the NPs.…”
Section: Amphiphilic Cbs For Drug Deliverymentioning
confidence: 99%
“…reported a coassemble of an CB[7]decorated poly(lactic acid) CB3 and poly(lactic-co-glycolic acid) (PLGA) based NPs as a novel drug delivery platform. [68] A hydrophobic anticancer drug PTX was loaded into the NPs. Furthermore, CB3 on the surface of the NPs allowed facile, modular surface modification by a variety of functional moieties or tags that are linked with amantadine: folateamantadine (FA-ADA) were able to target to folate receptor overexpressed cell line; fluorescein isothiocyanate-amantadine (FA-ADA) was used to fluorescence trackable delivery in cells; PEG-amantadine (PEG-ADA) can decrease phagocytosis by macrophage; and oxaliplatin (OX) for synergistic therapy against cancer cells (Figure 18).…”
Section: Amphiphilic Cbs For Drug Deliverymentioning
confidence: 99%
“…Nevertheless, the heterogeneization of the recognition properties can be achieved not only by CDs, but also by other type of hosts. For example, it was demonstrated that cucurbit[7]uril (CB[7]), can be used to decorate polylactic acid (PLA) and poly(lactic‐ co ‐glycolactic) acid (PLGA) nanoparticles . This CB[7] addition provides to the particles with specific recognition sites for the loading of secondary drugs such as oxaliplatin, turning this nanoparticles into a biocompatible and versatile drug delivery platform.…”
Section: Recognition Process Using Macrocyclesmentioning
confidence: 99%
“…[12,[15][16][17][18][19][20][21] Supramolecular strategy has been widely used to construct biomaterials for therapeutic or bioimaging purpose. [22][23][24][25][26][27][28][29][30][31] One key challenge for supramolecular strategy is the stability under PAA via ester and amide linkers to yield PAA-CB [6] and PAA-CPMA, respectively (Figure 1b). MSN was functionalized by CPMA-moiety with GSH-cleavable disulfide linkers.…”
Section: Introductionmentioning
confidence: 99%